Decision-making and its relationship to spiking and blocking performance in volleyball for emerging players - Malath Haider; Dr. Njlaa Abbas (الرياضة المعاصرة, 2021)
The game of volleyball is one of the competitive team games that took the lead in terms of its spread in the world, and the game of volleyball relies on basic skills as an important base on which this game is built to advance in the level of performance Performance and among these skills the skill of spiking and blocking wall, the research aims to identify the extent of the relationship of decision-making to the performance of spiking and blocking in volleyball for junior players. The sample was chosen from volleyball players for the Junior Specialized School of Sulaikh Sports Club / Baghdad Governorate for the season 2020 The researcher used the descriptive approach, and the research community was composed of (101) players. The two researchers prepared a decision-making scale consisting of 22 items. Percentages were calculated, the arithmetic average and hypothesis were calculated. The reliability coefficient was found using the half-segmentation method and Alpha Cronbach to know the test stability and correlation coefficient. Pearson Validity Discrimination of Paragraphs and the t-test In light of the results of the research, conclusions were reached, where the critical thinking of the players was found to have a positive relationship in the skills of hitting and crushing wall. The researcher also recommends conducting more research on decision-making skills in other variables in the game of volleyball.